ANALISIS KOMPETENSI PEDAGOGIK GURU DALAM MENINGKATKAN HASIL BELAJAR SOSIOLOGI DI KELAS X MAS AL-JIHAD PONTIANAK - Muthmainnah, Muthmainnah; Supriadi, Supriadi; Salim, Izhar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research was to determine the pedagogical competence of teachers in improving learning outcomes in sociology subjects in class X of MAS AL-Jihad Pontianak. The purpose of this study was to determine the pedagogical competence of teachers in improving learning outcomes in sociology subjects in class X MAS AL-Jihad Pontianak. The method that will be used in this research is descriptive. Data collection techniques that will be used are observation, interview, and documentation study techniques. While the data collection tool that will be used is an observation guide, interview guide, and documentation.Â Keywords: Pedagogic Competence, Sociology Teacher, Learning Outcome